BRASIL, o disco: representação e memória a partir da música extrema e periférica do Ratos De Porão (1981-1989) - QUADROS SOUZA, Renan Marchesini. (2022)
Formed in 1981, in Piauí village, a peripheral neighborhood in the North Zone of São Paulo, Basement Rets (In Portuguese: Ratos De Porão - R.D.P.) transited through several subgenres of extreme music, the band inaugurated the crossover in Brazil. Created in the bases of punk rock, the group never abandoned the essential characteristics of the movement, such as the defiant attitude and the lyrics linked to social reality. As members of the working and subaltern classes, they observe reality and narrate it in their work in a peculiar way. This work aims to investigate how the R.D.P. articulates forms of representation of historical, social and memory facts through its music, lyrics and album covers. To try to answer this question, we opted for a qualitative research methodology, we approached the study of musical compositions, lyrics, graphic-visual elements of five albums, considering the band's production in the period from 1983 to 1989. The theoretical references that support this investigation is the studies of popular music in communication, the studies of memory in communication, the semiotics of culture and the notion of representation in cultural studies. The realization states that the investigation of Basement Rets makes direct relationships with social reality. This means that the group's art, through the music, the lyrics and the covers of their records, built senses of memory about Brazil. The center of the analysis is the album Brasil (1989) where we can verify mnemonic representations from the cover to the lyrics, in addition to the sound definition of the crossover(AU)